Different and overlapping functions of Arabidopsis LHT6 and AAP1 transporters in root amino acid uptake - Perchlik, Molly (Journal of experimental botany, 2014)
© The Author 2014. Published by Oxford University Press on behalf of the Society for Experimental Biology.